Estudio de las estrategias de redes sociales de la Dirección de Gestión de Turismo y su impacto en el flujo turístico de la ciudad de Riobamba. - Ortiz Yar, Adrian Stefano (2025)
This study addresses the limitations in the social media strategies employed by the Riobamba tourism management directorate across various digital platforms. The research explores the relationship between social media strategies and tourist influx, utilizing analytical tools to measure their effectiveness. The study examines how social media strategies impact tourism flow in the city, applying both quantitative and qualitative approaches, as social media serves as a crucial tool for promoting a destination's attractions. Findings reveal that the implemented social media strategies have contributed to attracting tourists and positioning Riobamba as an appealing destination. The most utilized platforms include TikTok, Instagram, and Facebook, where visually engaging and informative content has achieved significant viewership. Among the key findings, the study identified the need for more visually compelling strategies to capture the attention of Riobamba Truism’s social media audience. Based on the research results, a proposal was developed to integrate drone technology, enhancing the impact of audiovisual content on social media. This approach effectively showcases the city's beauty and authenticity, fostering greater user engagement with published content.